Sectoral aid priorities: Are donors really doing their best to achieve the millennium development goals? - Rainer Thiele; Peter Nunnenkamp; Axel Dreher (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
We analyze the aid portfolio of various bilateral and multilateral donors, testing whether they have prioritised aid in line with the Millennium Development Goals (MDGs). In doing so, we combine sectorally disaggregated aid data with indicators reflecting the situation of recipient countries regarding the MDGs. Our results show that donors differ not only in terms of their overall generosity and the general poverty orientation of aid, but also in the extent to which their sectoral aid allocation is conducive to achieving more specific MDGs such as all children completing a full course of primary schooling, reducing child and maternal mortality as well as reversing the spread of HIV/AIDS. Overall, while some MDGs, e.g., the fight against HIV/AIDS, have shaped the allocation of aid, the sector-specific results reveal that with respect to other MDGs, most notably primary education, there is a considerable gap between donor rhetoric and actual aid allocation. These results invite the conclusion that the current focus on substantially increasing aid in order to turn the tide in trying to achieve the MDGs misses one important point: Unless the targeting of aid is improved, higher aid will not have the desired effects. Our results suggest that at least part of the blame for missing the MDGs falls on insufficient targeting of aid.
Keywords: F35; O11; O19; 330; MDGs; Development Aid; Aid Allocation